PENGARUH TERAPI SENTUH TERHADAP PENINGKATAN SUHU TUBUH PADA BAYI BARU LAHIR NORMAL - Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga (JURNAL ILMIAH DHDT - KEBIDANAN, 2018)
Abstract Background: Temperature changes occur early in the life of a newborn are an adaptation process that newborns must be passed in the beginning of his life. Touch therapy is an alternative non-pharmacological method that can help temperature stability in normal newborns. Purpose: This study aims to examine to effect of touch therapy increase temperature in newborns. Method: This study was a quasi-experimental with pre and post test, conducted in the Deli Serdang Public Hospital. There were 16 participants selected using purposive sampling. Data were analyzed using paired t test. Results: There were statically significant effect of temperature before and after touch theraphy with p value 0,001. The increasing of temperature through touch therapy is 40.1%. Conclusion: Touch theraphy has a significant effect in increasing temperature in newborns. The intervention could be apllied as an alternative theraphy in treating newborns.